Perlawanan Ulama dan Petani terhadap Kebijakan Kenaikan Pajak oleh Pemerintah Kolonial Belanda di Cimarame Garut, 1919 - Nafi, Moh. Iqbal; Badrun, Badrun (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This research examines the Cimareme Incident in Garut as a resistance to Dutch colonialism in the early 20th century. Through qualitative qualitative historical method, this research traces the socio-economic background of the Cimareme of the Cimareme people who were mostly farmers, as well as the oppressive colonial policies such as the obligation to sell rice, which triggered resistance from the Cimareme people led by Haji Hasan Arif. The people of Cimareme, who were mostly farmers, lived under the pressure of colonial economic policies that forced them to sell their crops at disadvantageous prices. This research was conducted through the stages of data collection or heuristics from literature sources, verification of the validity of sources, interpretation of historical facts, and historiography. The results revealed that the Cimareme Incident was not only a resistance to colonial policies that harmed farmers, but also showed the strong spirit of nationalism among the Garut people. This resistance showed how religious figures, especially Haji Hasan Arif, played an important role in mobilizing the people to uphold justice and fight against colonial exploitation. Although this resistance was followed by the arrest and suppression of Kyai, Peasants, Santri, and Hajis, this event became an important symbol in the struggle for Indonesian independence. The Cimareme Incident strengthened the collective consciousness of the community to unite against colonialism and showed how religion and nationalism became a driving force in the struggle towards independence.